2002
DOI: 10.1046/j.1365-313x.2002.01319.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of a GFP reporter gene for Chlamydomonas reinhardtii chloroplast

Abstract: SummaryReporter genes have been successfully used in chloroplasts of higher plants, and high levels of recombinant protein expression have been reported. Reporter genes have also been used in the chloroplast of Chlamydomonas reinhardtii, but in most cases the amounts of protein produced appeared to be very low. We hypothesized that the inability to achieve high levels of recombinant protein expression in the C. reinhardtii chloroplast was due to the codon bias seen in the C. reinhardtii chloroplast genome. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
146
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 179 publications
(150 citation statements)
references
References 39 publications
2
146
0
2
Order By: Relevance
“…Northern blots indicated that the increase of codon-optimized CNTB-FVIII HC and CNTB-VP1 accumulation is at the translational level rather than RNA transcript accumulation. Several previous studies on the expression of foreign genes have shown a lack of variation or modest increases in transcript abundance but significant variation in translation efficiency (Franklin et al, 2002;Gisby et al, 2011;Nakamura et al, 2016). Franklin et al (2002) reported a lack of variation in transcript abundance for GFP expression in Chlamydomonas reinhardtii chloroplasts despite an 80-fold increase in GFP protein accumulation of the codonoptimized sequence.…”
Section: Translation Efficiency Of Native and Codon-optimized Genes Imentioning
confidence: 97%
See 3 more Smart Citations
“…Northern blots indicated that the increase of codon-optimized CNTB-FVIII HC and CNTB-VP1 accumulation is at the translational level rather than RNA transcript accumulation. Several previous studies on the expression of foreign genes have shown a lack of variation or modest increases in transcript abundance but significant variation in translation efficiency (Franklin et al, 2002;Gisby et al, 2011;Nakamura et al, 2016). Franklin et al (2002) reported a lack of variation in transcript abundance for GFP expression in Chlamydomonas reinhardtii chloroplasts despite an 80-fold increase in GFP protein accumulation of the codonoptimized sequence.…”
Section: Translation Efficiency Of Native and Codon-optimized Genes Imentioning
confidence: 97%
“…Several previous studies on the expression of foreign genes have shown a lack of variation or modest increases in transcript abundance but significant variation in translation efficiency (Franklin et al, 2002;Gisby et al, 2011;Nakamura et al, 2016). Franklin et al (2002) reported a lack of variation in transcript abundance for GFP expression in Chlamydomonas reinhardtii chloroplasts despite an 80-fold increase in GFP protein accumulation of the codonoptimized sequence. Even though there was a 3-fold increase in mRNA levels of codon-optimized TGF-b3 when compared with the native sequence (Gisby et al, 2011), the greater part of the 75-fold increase in synthetic TGF-b sequence was attributed to enhanced translation.…”
Section: Translation Efficiency Of Native and Codon-optimized Genes Imentioning
confidence: 97%
See 2 more Smart Citations
“…The native hGAD65 DNA contains relatively low AT content (52%) and its expression may not be favored by an AT-rich C. reinhardtii chloroplast genome in which the overall AT content is 65.5% [43]. Franklin et al [44] showed an 80-fold increase in expression levels of GFP (green fluorescent protein) in C. reinhardtii chloroplasts when a synthetic GFP gene with increased AT content (66% AT content in synthetic GFP in comparison to native GFP with 60% AT content) was used. Furthermore, as the 5'-UTR region of chloroplast mRNAs has a profound effect on the translational efficiency of C. reinhardtii chloroplast genes [45,46], the use of different 5'-UTRs of chloroplast genes such as the 5'-UTR of the plastid psbA gene (D1 protein of photosystem II), combined with a strong promoter, could serve as another approach to enhance hGAD65 expression in C. reinhardtii cells.…”
Section: Discussionmentioning
confidence: 99%